The Relation of Shari'a, Tariqat, and Haqiqat in the Perspective of Badiuzzaman Said Nursi - Syamsuri, Syamsuri; Fawaid, Ahmad; Khoir, Nadiatul (JURNAL ISLAM NUSANTARA, 2022)
This study aims to describe how Badiuzzaman Said Nursi views the relation of shari'a, tariqat, and haqiqat and how the concept of Badiuzzaman Said Nursi in his Sufism journey and what is behind the birth of the concept of Sufism. The method used in this research is qualitative with the type of library research. The study results show that Nursi's view of the relation of shari'a, tariqat, and haqiqat cannot be separated from one another because all three are three paths with one goal. Nursi abbreviated several concepts in his Sufism journey with four concepts sourced from the Qur'an, including weakness (al-'Ajz), poverty (al-Faqr), and compassion (al-Syafaqah), thinking and contemplating (Tafakkur). Something behind Badiuzzaman Said Nursi in his Sufism revitalization discourse is due to the rampant deviations committed by Sufistic practitioners in Turkey.